2000
DOI: 10.1016/s0014-5793(00)01530-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular chaperone properties of serum amyloid P component

Abstract: The selective binding of serum amyloid P component (SAP) to proteins in the pathological amyloid cross-L L fold suggests a possible chaperone role. Here we show that human SAP enhances the refolding yield of denatured lactate dehydrogenase and protects against enzyme inactivation during agitation of dilute solutions. These effects are independent of calcium ions and are not inhibited by compounds that block the amyloid recognition site on the B face of SAP, implicating the A face and/or the edges of the SAP pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 22 publications
(24 reference statements)
2
45
0
Order By: Relevance
“…It is therefore likely that bulk processing of non-native proteins is dealt with by much more abundant proteins with chaperone properties, herafter referred to as extracellular chaperones (ECs), which have only recently been identified. 16 have been shown to exhibit chaperone properties in vitro. The first three of these proteins share functional characteristics with the small heat shock proteins in that they are able to efficiently stabilize misfolded proteins to prevent them aggregating but are not capable of independently refolding proteins.…”
Section: Extracellular Chaperonesmentioning
confidence: 99%
“…It is therefore likely that bulk processing of non-native proteins is dealt with by much more abundant proteins with chaperone properties, herafter referred to as extracellular chaperones (ECs), which have only recently been identified. 16 have been shown to exhibit chaperone properties in vitro. The first three of these proteins share functional characteristics with the small heat shock proteins in that they are able to efficiently stabilize misfolded proteins to prevent them aggregating but are not capable of independently refolding proteins.…”
Section: Extracellular Chaperonesmentioning
confidence: 99%
“…Four secreted glycoproteins, clusterin , haptoglobin , α2-macroglobulin (French et al, 2007) and serum amyloid P component (SAP) (Coker et al, 2000), have been shown to exhibit chaperone properties in vitro. These four proteins share some notable similarities.…”
Section: Extracellular Chaperonesmentioning
confidence: 99%
“…However, one study showed that when added to a refolding buffer containing denatured lactate dehydrogenase (LDH), SAP markedly enhanced the yield of active LDH. The reaction was supra-stoichometric, as a ratio of SAP pentamer to LDH substrate of 10:1 was needed to recover 25% of enzyme reactivity (Coker et al, 2000). This suggests that SAP is an inefficient refolding-competent chaperone.…”
Section: Serum Amyloid P Componentmentioning
confidence: 99%
“…Further studies are needed before the potential physiological significance of this refolding activity becomes clear. SAP binds to synthetic Aβ at physiological concentrations of Ca 2+ [198] and binds to all types of amyloid fibrils tested in vitro [199]. SAP has a protease-resistant β-pleated sheet structure that in the presence of Ca 2+ is resistant to proteolysis [200].…”
Section: In Vitro Chaperone Activitymentioning
confidence: 99%